Fuyuan decoction prevents nasopharyngeal carcinoma metastasis by inhibiting circulating tumor cells/ endothelial cells interplay and enhancing anti-cancer immune response - Ye, Yuying; Lin, Mengting; Zhou, Guiyu; Wang, Weiyu; Yao, Yinyin; Su, Yafei; Qi, Jianqiang; Zheng, Yanfang; Zhong, Chunlian; Chen, Xi; Huang, Mingqing; Lu, Yusheng (Frontiers in Pharmacology, 2024)
Distant metastasis is a major cause of treatment failure in cancer patients and a key challenge to improving cancer care today. We hypothesized that enhancing anti-cancer immune response and inhibiting circulating tumor cells (CTCs) adhesion and transendothelial migration through synergistic multi-target approaches may effectively prevent cancer metastasis. "Fuyuan Decoction" (FYD) is a traditional Chinese medicine compound that is widely used to prevent postoperative metastasis in cancer patients, but its underlying mechanism remains unclear. In this work, we systematically elucidated the underlying molecular mechanism by which FYD prevents cancer metastasis through multi-compound and multi-target synergies in vitro and in vivo. FYD significantly prevented cancer metastasis at non-cytotoxic concentrations by suppressing the adhesion of CTCs to endothelial cells and their subsequent transendothelial migration, as well as enhancing anti-cancer immune response. Mechanistically, FYD interrupts adhesion of CTCs to vascular endothelium by inhibiting TNF-α-induced CAMs expression via regulation of the NF-κB signaling pathway in endothelial cells. FYD inhibits invasion and migration of CTCs by suppressing EMT, PI3K/AKT and FAK signaling pathways. Moreover, FYD enhances the anti-cancer immune response by significantly increasing the population of Tc and NK cells in the peripheral immune system. In addition, the chemical composition of FYD was determined by UPLC-HRMS, and the results indicated that multiple compounds in FYD prevents cancer metastasis through multi-target synergistic treatment. This study provides a modern medical basis for the application of FYD in the prevention of cancer metastasis, and suggesting that multi-drug and multi-target synergistic therapy may be one of the most effective ways to prevent cancer metastasis.